Impact of Job Stress and Burnout on Employee Satisfaction and Performance in the Work Environment - Abadi, Indra; Hasanuddin, Hasanuddin (Journal of Economics Review (JOER), 2024)
This study investigates the impact of job stress and burnout on employee satisfaction and performance in organizational settings. By examining these factors, the research aims to understand how stress and burnout affect workforce engagement, productivity, and overall organizational health. The study employs a systematic literature review (SLR) approach, integrating findings from various disciplines, including human resource management, organizational behavior, and occupational psychology. This method allows for a structured synthesis of existing knowledge, focusing on key concepts, theoretical frameworks, and empirical evidence. The findings reveal that high job stress and burnout correlate with reduced employee satisfaction and diminished individual and team performance. Chronic stress and burnout lead to emotional exhaustion, lower productivity, and increased turnover risk. The study also identifies organizational interventions—such as supportive leadership, stress management training, and recognition programs—that can effectively mitigate these adverse outcomes. Furthermore, variations in industry pressures and employee demographics influence the stress and burnout experienced, highlighting the need for tailored organizational strategies. This study's results have significant implications for academic and managerial practices. Academically, the research deepens the theoretical understanding of stress and burnout dynamics. It provides a basis for implementing data-driven stress management initiatives, enhancing job satisfaction, and improving workforce resilience. Organizations can leverage these findings to create healthier work environments, boost productivity, and strengthen their competitive edge.